Aerospace series. Heat resisting nickel base alloy (NI- P100HT). Cold worked and softened. Bar and wire for continuous forging or extrusion for fasteners. 3 mm ≤ D ≤ 30 mm. (6th March 2020) - British Standards Institution,
No abstract available